Representing Islam: Experiences of women wearing hijab in New Zealand - Ash E; Tuffin K; Kahu E (New Zealand Psychological Society Inc)
An increase in commentary on the hijab, or Muslim headscarf, in Western countries can be attributed to multiple factors, not least among them the current political discourse relating to Islamic terrorism (Green, 2015). Despite Islam being a rapidly expanding religion in New Zealand, there is a dearth of research pertaining to Muslims. Here we aim to understand the everyday experiences of hijabi women in New Zealand. Six women were interviewed, and the data were analysed using an interpretive phenomenological framework. Three themes were identified: explanations for wearing hijab, interpersonal experiences, and the responses to these interpersonal experiences. Research findings point to a complex interplay of individual and socio-cultural factors which influence the everyday experiences of hijabi women.
Keywords: hijab; Muslim; Islam; discrimination; prejudice